Protective Effects of Dietary Capsaicin on the Initiation Step of a Two-Stage Hepatocarcinogenesis Rat Model - Sarmiento-Machado, Luis Manuel [UNESP]; Romualdo, Guilherme Ribeiro [UNESP]; Zapaterini, Joyce Regina [UNESP]; Tablas, Mariana Baptista [UNESP]; Fernandes, Ana Angélica Henrique [UNESP]; Moreno, Fernando Salvador; Barbisan, Luís Fernando [UNESP] (Taylor & Francis, 2020)
Capsaicin (CPS), an ingredient of Capsicum plants, has anti-inflammatory, antioxidant and antitumoral properties. The mechanisms of CPS on hepatocarcinogenesis preclinical bioassays are not described. Thus, the protective effects CPS were evaluated in the early stages of chemically-induced hepatocarcinogenesis. Male Wistar rats received diet containing 0.01% or 0.02% CPS for 3 weeks. Afterwards, animals received a dose of hepatocarcinogen diethylnitrosamine (DEN, 100 mg/kg body weight). From weeks 4–12, groups had their diet replaced by a 0.05% phenobarbital supplemented one to promote DEN-induced preneoplastic lesions. Animals were euthanized 24 h after DEN administration (n = 5/group) or at week 12 (n = 9/group). The estimated CPS intake in rats resembled human consumption. At the end of week 3, dietary 0.02% CPS attenuated DEN-induced oxidative damage and, consequently, hepatocyte necrosis by reducing serum alanine aminotransferase levels, liver CD68-positive macrophages, lipid peroxidation, while increasing antioxidant glutathione system. Additionally, 0.02% CPS upregulated vanilloid Trpv1 receptor and anti-inflammatory epoxygenase Cyp2j4 genes in the liver. Ultimately, previous 0.02% CPS intake decreased the number of GST-P-positive preneoplastic lesions at week 12. Thus, CPS attenuated preneoplastic lesion development, primarily by diminishing DEN-induced oxidative liver injury. Findings indicate that CPS is a promising chemopreventive agent when administered after and during the early stages of hepatocarcinogenesis.